The Galerkin Method for Fourth-Order Equation of the Moore–Gibson–Thompson Type with Integral Condition - Ahlem Mesloub; Abderrahmane Zaraï; Fatiha Mesloub; Bahri-Belkacem Cherif; Mohamed Abdalla (Advances in Mathematical Physics)
In this manuscript, we consider the fourth order of the Moore–Gibson–Thompson equation by using Galerkin’s method to prove the solvability of the given nonlocal problem.